2014
DOI: 10.1111/jth.12571
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps form predominantly during the organizing stage of human venous thromboembolism development

Abstract: Background A growing health problem, venous thromboembolism (VTE), including pulmonary embolism (PE) and deep vein thrombosis (DVT), requires refined diagnostic and therapeutic approaches. Neutrophils contribute to thrombus initiation and development in experimental DVT. Recent animal studies recognized neutrophil extracellular traps (NETs) as an important scaffold supporting thrombus stability. However, the hypothesis that human venous thrombi involve NETs has not undergone rigorous testing. Objective To ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
189
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 42 publications
2
189
2
3
Order By: Relevance
“…1 The role of neutrophils became evident by using an antibody-mediated depletion strategy identical to the method used in this study (depletion of Ly6G-positive cells). For the electrolytic inferior vena cava model of VT in which the vena cava is directly activated by an electric current thus causing endothelial damage, it was demonstrated that vein wall neutrophils were the most common cell type present in acute VT. 20 Moreover, neutrophils and NETs have also been identified in human VT. 21,22 When VT followed silencing of anticoagulant genes, Ly6G-positive neutrophils were abundantly present within the thrombi, seemingly recruited and aligned to the fibrin layers, which is consistent with previous observations. 1,2 However, in our model, neutrophils were not rate limiting in thrombus formation.…”
Section: Discussionsupporting
confidence: 80%
“…1 The role of neutrophils became evident by using an antibody-mediated depletion strategy identical to the method used in this study (depletion of Ly6G-positive cells). For the electrolytic inferior vena cava model of VT in which the vena cava is directly activated by an electric current thus causing endothelial damage, it was demonstrated that vein wall neutrophils were the most common cell type present in acute VT. 20 Moreover, neutrophils and NETs have also been identified in human VT. 21,22 When VT followed silencing of anticoagulant genes, Ly6G-positive neutrophils were abundantly present within the thrombi, seemingly recruited and aligned to the fibrin layers, which is consistent with previous observations. 1,2 However, in our model, neutrophils were not rate limiting in thrombus formation.…”
Section: Discussionsupporting
confidence: 80%
“…Staining of human acute PE specimens for CD42b, a platelet surface membrane glycoprotein, has demonstrated a high concentration of platelets in venous thrombus. 15 This observation challenges a long-held belief that platelets play little role in the pathogenesis of VTE.…”
contrasting
confidence: 43%
“…Furthermore, polymorphisms in genes encoding factor VII, interleukin-1␤ (IL-1␤), and IL-10 modulate the risk of idiopathic VTE (11 ). The presence of neutrophils and neutrophil extracellular traps in human venous thrombus further highlight the importance of inflammation to the development of VTE (12 ).…”
mentioning
confidence: 99%